2022
DOI: 10.3389/fgene.2021.784811
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Metabolism-Related Genes in Plateau Pika (Ochotona curzoniae) at Different Altitudes on the Qinghai–Tibet Plateau

Abstract: According to life history theory, animals living in extreme environments have evolved specific behavioral and physiological strategies for survival. However, the genetic mechanisms underpinning these strategies are unclear. As the highest geographical unit on Earth, the Qinghai–Tibet Plateau is characterized by an extreme environment and climate. During long-term evolutionary processes, animals that inhabit the plateau have evolved specialized morphological and physiological traits. The plateau pika (Ochotona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 103 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…In this study, considering that gender differences will affect the results, we used the results of heart tissue expression of Gansu pika (including five females and nine males) to analyse the differences between different genders, and the results showed that there was no significant difference. Other transcription studies of pika heart and lung tissue have also not considered the effect of gender on the results ( Zhang et al, 2022 ; Zhu et al, 2022 ). Therefore, instead of sex typing of plateau pikas and Gansu pikas, we directly analysed the transcriptome of heart tissues of 28 samples in order to explore the potential genetic mechanism of plateau pikas adapting to high altitude environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, considering that gender differences will affect the results, we used the results of heart tissue expression of Gansu pika (including five females and nine males) to analyse the differences between different genders, and the results showed that there was no significant difference. Other transcription studies of pika heart and lung tissue have also not considered the effect of gender on the results ( Zhang et al, 2022 ; Zhu et al, 2022 ). Therefore, instead of sex typing of plateau pikas and Gansu pikas, we directly analysed the transcriptome of heart tissues of 28 samples in order to explore the potential genetic mechanism of plateau pikas adapting to high altitude environment.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al (2008) showed that plateau pikas can improve their adaptation to anoxic environments by increasing the density of heart mitochondria and the microvasculature and myoglobin contents. Zhu et al (2021) measured the resting metabolic rate and transcriptional expression levels of adipose tissue, liver and skeletal muscle in pikas along different elevation gradients and proved that plateau pikas could adapt to the extreme environment of the QHTP through increases in the expression of thermogenesis genes and energy metabolism. However, current research on the high-altitude adaptation of pikas is mainly focused on nonshivering thermogenesis ( Wang et al, 1999 ; Wang et al, 2006 ), the regulation of skeletal muscle lactate dehydrogenase-c, liver hypoxia and pulmonary circulation ( Liu et al, 2012 ; Melo Ferreira et al, 2015 ; Pichon et al, 2015 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four rounds of metabolism were measured in 120 min, with each round lasting for 30 min. We obtained the average of the lowest consecutive records as the RMR (Zhu et al, 2021).…”
Section: Resting Metabolic Rate (Rmr)mentioning
confidence: 99%
“…Meanwhile, in vertebrates, gut microbiota compositional differences among species are positively correlated with the evolutionary divergence time of the host, and the gut microbiota composition is more similar within host species than among species (Moeller et al, 2017;Song et al, 2020;Dillard et al, 2022). Additionally, environmental factors have been confirmed to be closely related to the gut microbiota structure (Ley et al, 2008;Zhao et al, 2018) and the extreme cold, the dry, hostile climate of high altitude environments, high ultraviolet radiation, and low oxygen content have important effects on the cardiovascular system, energy metabolism, and body temperature retention of animals (Simonson et al, 2010;Yu et al, 2016;Zhu et al, 2021). A variety of mammalian gut microbiota also respond to this environmental pressure, forming a composition of gut microbiota that adapts to the high altitude environments, and play an important role in host food digestion, energy metabolism, nutritional homeostasis, immune regulation, signal transduction, and other physiological activities (Bäckhed et al, 2005;Ley et al, 2006;Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%